2021
DOI: 10.47312/aar.v5i02.309
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Related Party Transactions and Earnings Management

Abstract: <em>This study aimed to examine the relationship between related party transactions and earnings management. The sample of this study was companies listed on the Indonesia Stock Exchange for the 2017 and 2018 period. The result shows that related party transaction (sales and expense) has a negative effect on accrual earnings management. It indicates that firms use related party transactions (sales and expense) as substitutes for earnings management especially accrual earnings management.</em>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Strong research documents in the Iran market have confirmed that carrying out RPTs by Iranian firms can lead to the loss of shareholder wealth, which is in line with the tunneling hypothesis (Zimon et al 2021). For example, the results of Sarlak and Akbari (2014), as well as Ghannad et al (2018), show a positive connection between RPTs and profit distortion. Both of them argue that due to the separation of ownership from management and the existence of a conflict of interest between them, RPTs in Iran's context lead to the loss of shareholder wealth, and the Iranian managers tend to manage profits to cover up this transfer of wealth.…”
Section: The Relationship Between Related Party Transactions and Fina...mentioning
confidence: 59%
See 1 more Smart Citation
“…Strong research documents in the Iran market have confirmed that carrying out RPTs by Iranian firms can lead to the loss of shareholder wealth, which is in line with the tunneling hypothesis (Zimon et al 2021). For example, the results of Sarlak and Akbari (2014), as well as Ghannad et al (2018), show a positive connection between RPTs and profit distortion. Both of them argue that due to the separation of ownership from management and the existence of a conflict of interest between them, RPTs in Iran's context lead to the loss of shareholder wealth, and the Iranian managers tend to manage profits to cover up this transfer of wealth.…”
Section: The Relationship Between Related Party Transactions and Fina...mentioning
confidence: 59%
“…In fact, sometimes a transaction is made to gain access to the experience, expertise, and unique skills of a related party or to compensate for services, in which case there is no incentive to manage profits (Gordon and Henry 2005). In the same vein, various studies so far have shown that there is no specific incentive to manage profits when dealing with a related party (Kuan et al 2010;Jian and Wong 2010;El-Helaly et al 2018;Alhadab et al 2020;Sari et al 2021).…”
Section: The Relationship Between Related Party Transactions and Fina...mentioning
confidence: 99%
“…There is also evidence (Kohlbeck et al, 2018) that family firms are more prone to enter into RPTs and that their financial performance declines when they report transactions with directors, officers and major shareholders. When opportunistic RPTs are put in place, managers may resort to EM practices to increase the benefits extracted or to disguise the expropriations perpetrated to the detriment of outsiders (Sarlak and Akbari, 2014;Marchini et al, 2018). Studies focusing on emerging markets have pointed out that RPTs exacerbate REM, but family ownership moderates this opportunistic association (Haji-Abdullah and Wan-Hussin, 2015).…”
Section: Earnings Management Rpts and Family Firmsmentioning
confidence: 99%
“…, 2018) that family firms are more prone to enter into RPTs and that their financial performance declines when they report transactions with directors, officers and major shareholders. When opportunistic RPTs are put in place, managers may resort to EM practices to increase the benefits extracted or to disguise the expropriations perpetrated to the detriment of outsiders (Sarlak and Akbari, 2014; Marchini et al. , 2018).…”
Section: Theoretical Framework Literature Review and Hypotheses Devel...mentioning
confidence: 99%
“…This is often prompted by the pressure from analysts and investors (Shin et al, 2021). RPTs are also used to manipulate accruals in a company and thus change the financial performance reports to show a better picture (Sari et al, 2020).…”
Section: Related Party Transactionsmentioning
confidence: 99%